Law of the Sea. - Glassner, Martin Ira (1989)
Keywords: dept.egm; faculty_collection; sabbatical_report

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Academic Publishers, 1986)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

International Law of the Sea and Marine Affairs: A Bibliography. Supplement to the 1980 Edition - Papadakis, N.; Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Boston, 1984)
Keywords: Bibliography; Maritime law; dept.egm; faculty_collection

Global Resources: Challenges of Interdependence - Glassner, Martin Ira (Published for the Foreign Policy Association by Praeger, 1983)
SCSU Faculty Scholar Award
Keywords: Natural resources; award_winner; dept.egm; faculty_collection

Baseline Shellfish Data for the Assessment of Potential Environmental Impacts Associated with Energy Activities in Connecticut's Coastal Zone - Pellegrino, Peter Edward; Hubbard, William A. (Southern Connecticut State University Foundation, 1983)
Keywords: Connecticut Coastal Energy Impact Program; Shellfish populations; Effect of oil spills on; Environmental aspects; Long Island Sound (N.Y. and Conn.); Long Island Sound (N.Y. and Conn.); Aquatic ecology; Long Island Sound (N.Y. and Conn.); Energy industries; Long Island Sound (N.Y. and Conn.); Petroleum products; Long Island Sound (N.Y. and Conn.); Shellfish; Research; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (Sijthoff & Noordhoff, 1980)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Maritime law; dept.egm; faculty_collection

Systematic Political Geography - Glassner, Martin Ira; De Blij, Harm J. (Wiley, 1980)
Keywords: Political geography; Geopolitics; dept.egm; faculty_collection

The Life and Thought of Isaiah Bowman. - Martin, Geoffrey J. (1980)
SCSU Faculty Scholar Award
Keywords: Biography; Bowman; Isaiah; 1878-1950; Geographers; United States; award_winner; dept.egm; faculty_collection

Systematic political geography. 4th edition - Glassner, M.I.; De Blij, H.J. (Systematic political geography. 4th edition, 1988)
The fourth edition of this text has been thoroughly updated and includes expanded chapters on Antarctica and outer space as well as new chapters on the geography of elections and the geography of war and peace. A chapter is devoted to outlaws and merchants of death which covers piracy, drug trafficing, the arms trade, and terrorism. Other additions include coverage of international economic sanctions, transnational corporations, refugees, and pollution across international boundaries. -from Publisher
Keywords: arms trade; dept.egm; economic sanctions; elections; peace; political geography; pollution; refugees; terrorism; war; ⛔ No DOI found

Classifying Aquatic Habitats - Smith, D.G.; Leskowitz, I. (American Biology Teacher, 1987)
1 citations (Crossref) [2023-10-31]
Keywords: dept.egm

John Paul Goode, 1862-1932. - Martin, G.J. (Geographers: biobibliographical studies, vol. 8, 1984)
In 1901 Goode obtained his doctorate - only the second in the USA to break away from the geology/physiography tradition. As his career developed he increasingly specialized in cartography, developed coloured wall maps for Rand McNally, and an interrupted homolosine projection. His name has survived on a school atlas for over 60 years. There is a chronological bibliography and a summary of his life.-K.Clayton
Keywords: dept.egm; ⛔ No DOI found

Geography, its history and concepts - a students guide - holtjensen,a - Martin, GJ (Professional Geographer, 1989)
tex.unique-id: ISI:A1989CW63500027
Keywords: dept.egm; ⛔ No DOI found

Geography in Peru - Yacher, Leon (The Professional Geographer, 1989)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-013-298-750-435 tex.type: [object Object]
Keywords: dept.egm

Review: A Social and Economic Atlas of India - Muthiah,s - Yacher, Leon (American Cartographer, 1989)
tex.unique-id: ISI:A1989AD47200006
Keywords: dept.egm; ⛔ No DOI found

British geography 1918-1945 - steel,rw - Martin, GJ (Professional Geographer, 1989)
tex.unique-id: ISI:A1989R960900049
Keywords: dept.egm; ⛔ No DOI found

On whittlesey, bowman and harvard - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/194-741-197-626-019 tex.type: [object Object]
Keywords: dept.egm

Preston E. James, 1899–1986 - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/034-021-593-801-31X tex.type: [object Object]
Keywords: dept.egm

Against presentist histories: solot's view of sauer - Speth, William W (Annals of The Association of American Geographers, 1987)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-534-127-566-295 tex.type: [object Object]
Keywords: dept.egm

International regulation of whaling - from conservation of whaling to conservation of whales and regulation of whale-watching - birnie,p - Glassner, MI (Ocean Development and International Law, 1987)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1987K101500006
Keywords: dept.egm

The ecologic tradition in american geography 1895–1925 - Martin, Geoffrey J (Canadian Geographer, 1987)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-877-891-516-111 tex.type: [object Object]
Keywords: dept.egm

On the discrimination of Anthropo‐Geocraphies - Speth, William W (Canadian Geographer, 1987)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/074-321-118-839-576 tex.type: [object Object]
Keywords: dept.egm

Peru: the 1981 Census - Yacher, Leon (Geography, 1987)
Citation Key Alias: ISI:A1987G644700009 tex.unique-id: [object Object]
Keywords: dept.egm; ⛔ No DOI found

Recollections of a revolution - geography as spatial science - billinge,m, gregory,d, martin,r - Martin, GJ (Journal of Geography, 1986)
tex.unique-id: ISI:A1986D537100011
Keywords: dept.egm; ⛔ No DOI found

History of geography - geographer responds - Martin, GJ (National Geographic Research, 1986)
tex.unique-id: ISI:A1986AZK9500002
Keywords: dept.egm; ⛔ No DOI found

Book Review: steel, R.W. 1984: the institute of british geographers: the first fifty years. dor chester: henry ling-dorset press. ix + 170 pp. £12.00 - Martin, Geoffrey J. (Progress in Physical Geography, 1985)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1985ARR0500019 tex.unique-id: [object Object]
Keywords: book.review; dept.egm

Arctic technology and policy - dyer,i, chryssostomidis,c - Grassner, MI (Economic Geography, 1985)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1985ART1300014
Keywords: dept.egm

Paradigm change: a history of geography in the United States, 1892-1925. - Martin, G.J. (National Geographic Research, 1985)
The third of 5 paradigm periods posited for the history of American geography extends from the establishment of the Committee of Ten in 1892, to the publication of Carl Sauer's 'The Morphology of Landscape' in 1925. This period witnessed the emergence of discipline and profession - an inert physiography, energized by the discipline-forming Davisian cycle of erosion, preceded the causal notion. Determinisms that gave way to studies of control, adjustment, and the geographic factor, provided a framework for the geographic philosophies of such scholars as Albert Perry Brigham, Ellsworth Huntington, and Ellen Semple. Regional delimitations of physiographic provinces and variant forms of economic geography emerged as alternatives to causality. The geography of France, Germany, and Britain afforded little support for varieties of determinism in America, and was further questioned during the 1914-1918 war years. Meanwhile, Wellington D. Jones and Carl O. Sauer developed another viewpoint, adumbrated by Sauer in a series of papers culminating in 'The Morphology of Landscape'. The locus of American geography had been moved.-Author
Keywords: dept.egm; ⛔ No DOI found

Preservation of the history of geography - Martin, G.J. (Journal of Geography, 1985)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Perspective on ratzel political-geography - hunter,jm - Martin, GJ (Professional Geographer, 1985)
tex.unique-id: ISI:A1985ACX1700046
Keywords: dept.egm; ⛔ No DOI found

Selected Essays 1963-1975 - Sauer,carl,o. - Callahen,b - Martin, GJ (Professional Geographer, 1984)
tex.unique-id: ISI:A1984SR99000029
Keywords: dept.egm; ⛔ No DOI found

A history of modern british geography - freeman,tw - Martin, GJ (Annals of the Association of American Geographers, 1982)
tex.unique-id: ISI:A1982NT87500023
Keywords: dept.egm; ⛔ No DOI found

The history of the royal-geographical-society 1830-1980 - to the farthest ends of the earth - cameron,i - Martin, GJ (Progress in Human Geography, 1982)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1982PK80000024
Keywords: dept.egm

New haven, connecticut, from the air - Richason, F Benjamin; Yacher, Leon (Journal of Geography, 1981)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-405-597-813-713 tex.type: [object Object]
Keywords: dept.egm

Ethnology: A sociologia do brasil indígena. roberto cardoso de oliveira - Yacher, Leon (American Anthropologist, 1980)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/125-539-068-595-576 tex.type: [object Object]
Keywords: dept.egm

International-law for Antarctica - Francioni,f, Scovazzi,t - Glassner, MI (Marine Policy, 1989)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1989AT86700015
Keywords: dept.egm

The strait of dover, vol 8 - cuyvers,l - Glassner, MI (Journal of Maritime Law and Commerce, 1989)
tex.unique-id: ISI:A1989CD99200009
Keywords: dept.egm; ⛔ No DOI found

The un convention on the law of the sea - impact and implementation - proceedings of the 19th annual conference of the law-of-the-sea-institute, 1985 - brown,ed, churchill,rr - Glassner, MI (Marine Policy, 1989)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1989AT86700009
Keywords: dept.egm

Book Review: The law of the sea and maritime boundary delimitation in South-East Asia: Kriangsak Kittichaisaree Oxford University Press, Singapore, 1987, xv + 209 pp - Glassner, Martin Ira (Marine Policy, 1989)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/044-415-980-646-043 tex.type: [object Object]
Keywords: book.review; dept.egm

Marine affairs bibliography 1980-1985 - wiktor,cl, foster,la - Glassner, MI (Marine Policy, 1989)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1989AB91600012
Keywords: dept.egm

Book Reivew: Maritime boundaries and ocean resources: Gerald Blake (ed.), Croom Helm, Beckenham, Kent, 1987, xiii + 284 pp., £27.50 - Glassner, Martin I. (Political Geography Quarterly, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: International and United States documents on oceans law and policy: John Norton Moore (ed.), William S. Hein, Buffalo, NY, 1986, 5 vols., $195.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

The exclusive economic zone in international-law - attard,dj - Glassner, MI (Journal of Maritime Law and Commerce, 1989)
tex.unique-id: ISI:A1989U929600006
Keywords: dept.egm; ⛔ No DOI found

Book Review: The refugee problem on universal, regional and national level: Thesaurus Acroasium, Vol. XIII, Institute of International Public Law and International Relations of Thessaloniki, 1987, xvi + 1022pp., $150.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

United-nations convention on the law of the sea, 1982 - a commentary, vol 1 - nordquist,mh - Glassner, MI (Journal of Maritime Law and Commerce, 1989)
tex.unique-id: ISI:A1989T298200005
Keywords: dept.egm; ⛔ No DOI found

Georges bank - backus,rh - Glassner, MI (Canadian Geographer-Geographe Canadien, 1989)
tex.unique-id: ISI:A1989AU47200018
Keywords: dept.egm; ⛔ No DOI found

The atlas of Central-America and the Caribbean - diagram-group - Glassner, MI (Professional Geographer, 1987)
tex.unique-id: ISI:A1987J734400019
Keywords: dept.egm; ⛔ No DOI found

Book Review: The USSR, Eastern Europe and the development of the law of the sea: Compiled, Translated and Edited by W.E. Butler, Dobbs Ferry, NY: Oceana Publications, 1983 et seq. Two looseleaf binders, 100 each binder. - Glassner, Martin Ira (Political Geography Quarterly, 1987)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/069-757-450-223-358 tex.type: [object Object]
Keywords: book.review; dept.egm

Deep-sea mining and the law of the sea - post,am - Glassner, MI (Journal of Maritime Law and Commerce, 1987)
tex.unique-id: ISI:A1987G247500010
Keywords: dept.egm; ⛔ No DOI found

Law, force and diplomacy at sea - booth,k - Glassner, MI (Political Geography Quarterly, 1987)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1987F831400014
Keywords: dept.egm

The 7th continent - antarctica in a resource age - shapley,d - Glassner, MI (Economic Geography, 1987)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1987K626900014
Keywords: dept.egm

Review: africa: partitioned africans, african regional OrganizatonsPARTITIONED AFRICANS ethnic relations across africa's international boundaries, 1884–1984 edited by AsiwajuA.I.New york: st martin's press, 1985, xii, 275pp, US29.95AFRICAN REGIONAL ORGANIZATONS edited by MazzeoDomenicoNew york: cambridge university press, 1984, x, 265pp, US42.50 - Glassner, Martin Ira (International Journal, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: Geopolitics of the Caribbean: Ministates in a wider world: T.D. Anderson, Praeger, New York, 1984, xiii + 175 pp., $26.95 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: National interests and the military use of space: W.J. Durch (ed.), Ballinger, Cambridge, Mass, 1984, xiv + 304 pp., $28.00 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Management of Marine Regions - the North Pacific - Miles,e - Glassner, MI (Journal of Maritime Law and Commerce, 1986)
tex.unique-id: ISI:A1986E757600013
Keywords: dept.egm; ⛔ No DOI found

Managing the ocean - resources, research, law - richardson,jg - Glassner, MI (Marine Policy, 1986)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986E233300007
Keywords: dept.egm

United-states arctic interests - the 1980s and 1990s - westermeyer,we, shusterich,km - Glassner, MI (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986C186100010
Keywords: dept.egm

The Emerging Marine Economy of the Pacific - Gopalakrishnan,c - Glassner, MI (Professional Geographer, 1986)
tex.unique-id: ISI:A1986A260100040
Keywords: dept.egm; ⛔ No DOI found

The new political geography of the sea - Glassner, Martin Ira (Political Geography Quarterly, 1986)
The political geography of the sea may be defined as that portion of the Law of the Sea which has a spatial or territorial component, including such matters as the territorial sea and the contiguous zone, the exclusive economic zone, international straits, the regimes of islands and archipelagos, freedom of transit for land-locked states, deep seabed mining and protection and preservation of the marine environment. It also includes larger issues not formally part of the Law of the Sea, such as the links between the Law of the Sea and Antarctica, and military uses of the sea. The new Law of the Sea (hence the new political geography of the sea) is the latest stage in a long evolution traceable to the ancient Greeks and Romans but accelerating since the 17th century. The United Nations Conference on the Law of the Sea produced in 1958 four conventions essentially codifying the existing Law of the Sea, including the new continental shelf doctrine. They were followed by the 1965 UN Convention on Transit Trade of Land-locked States. All soon proved inadequate, unacceptable or obsolescent. The Third United Nations Conference on the Law of the Sea (UNCLOS III, 1973-1982) produced a new single, comprehensive convention embodying nearly all old and new aspects of the Law of the Sea. This and related matters deserve much greater attention from political geographers than they have received thus far. © 1986.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-537-247-901-750 tex.type: [object Object]
Keywords: dept.egm

Special issue - the new political-geography of the sea - Glassner, MI (Political Geography Quarterly, 1986)
2 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986AYH4000001
Keywords: dept.egm

Special issue - the new political-geography of the sea - panel discussion - Nanda, VP; Abrahamsson, BJ; Chiu, H; Alexander, LM; Glassner, MI; Earney, F; Engass, P; Knight, D; Jackson, R; Lynch, J; Morgan, J; Wolfe, L; et al. (Political Geography Quarterly, 1986)
tex.unique-id: ISI:A1986AYH4000007
Keywords: dept.egm; ⛔ No DOI found

Partitioned africans - ethnic-relations across africa international boundaries, 1884-1984 - asiwaju,ai - Glassner, MI (International Journal, 1986)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986G522000011
Keywords: dept.egm

Political geography of contemporary events VII: The view from the near north— South Americans view Antarctica and the Southern Ocean geopolitically - Glassner, Martin Ira (Political Geography Quarterly, 1985)
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/041-429-628-526-147 tex.type: [object Object]
Keywords: dept.egm

Command of the Sea - the History and Strategy of Maritime Empires - Reynolds,cg - Glassner, MI (Journal of Maritime Law and Commerce, 1985)
tex.unique-id: ISI:A1985AVR8100007
Keywords: dept.egm; ⛔ No DOI found

Superpower at sea - united-states ocean policy - laursen,f - Glassner, MI (American Political Science Review, 1985)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1985AEV4600105
Keywords: dept.egm

Change and development in the middle-east - clarke,ji, bowenjones,h - Glassner, MI (Journal of Developing Areas, 1984)
tex.unique-id: ISI:A1984ABS2000013
Keywords: dept.egm; ⛔ No DOI found

Contest for the south china sea - samuels,ms - Glassner, MI (Political Geography Quarterly, 1984)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1984TB24000008
Keywords: dept.egm

Land-locked states and the unclos regime - sinjela,am - Glassner, MI (American Journal of International Law, 1984)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1984TD35000028
Keywords: dept.egm

Mackinder - geography as an aid to statecraft - parker,wh - Glassner, MI (Professional Geographer, 1984)
tex.unique-id: ISI:A1984TE16200056
Keywords: dept.egm; ⛔ No DOI found

The Red-Sea and the Gulf of Aden - Lapidotheschelbacher,r - Glassner, MI (Political Geography Quarterly, 1984)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1984TQ87300015
Keywords: dept.egm

The transit problems of landlocked states: the cases of bolivia and paraguay - Glassner, Martin Ira (Ocean Yearbook Online, 1983)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-873-417-533-990
Keywords: dept.egm

Petroleum and hard minerals from the sea - earney,fcf - Glassner, MI (Professional Geographer, 1983)
tex.unique-id: ISI:A1983QG21700035
Keywords: dept.egm; ⛔ No DOI found

The legal regime of international rivers and lakes - zacklin,r, caflisch,l - Glassner, MI (Political Geography Quarterly, 1983)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1983RC47500012
Keywords: dept.egm

Book Review: ocean yearbook 2 - Glassner, Martin Ira (Ocean Development and International Law, 1982)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-376-670-156-933 tex.type: [object Object]
Keywords: book.review; dept.egm

Book Review: Iran, saudi arabia, and the law of the sea; political interaction and legal development in the persian gulf . by MacDonald charles g.. (westport, conn.: greenwood press, 1980. pp. xv + 226. 28.50.) - Glassner, Martin Ira (American Political Science Review, 1981)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-864-427-070-693 tex.type: [object Object]
Keywords: book.review; dept.egm

Book Review: The middle eastern states and the law of the sea . by ali a. El-Hakim. (syracuse, N.Y.: syracuse university press, 1980. pp. xv + 293. 27.00.) - Glassner, Martin Ira (American Political Science Review, 1981)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/194-082-868-513-810 tex.type: [object Object]
Keywords: book.review; dept.egm